Coherence analysis in the myoclonus of corticobasal degeneration. - Grosse, P; Kühn, A; Cordivari, C; Brown, P (2003)
We investigated whether myoclonus in corticobasal degeneration (CBD) is cortical or subcortical in origin. Many authors have suggested that the myoclonus in CBD is a subtype of cortical myoclonus, despite the fact that back-averaging fails to detect a cortical correlate to spontaneous or action induced jerks and giant sensory evoked potentials are seldom found. Electroencephalographic-electromyographic (EEG-EMG) and EMG-EMG frequency analysis may be more sensitive to cortical drives when EMG bursts occur at a high frequency and at low amplitudes as in CBD. We evaluated EEG-EMG and EMG-EMG coherence and phase in 5 patients with clinically probable CBD and unilateral, action-induced and stimulus-sensitive myoclonus. We found negligible corticomuscular coherence despite a dramatically exaggerated EMG-EMG coherence. We conclude that an inflated EMG-EMG coherence is found in some patients with CBD and that this is unlikely to be due to an exaggerated cortical drive.